Test–retest reliability and task order effects of emotional cognitive tests in healthy subjects. Issue 7 (2nd October 2016) - Adams, Thomas; Pounder, Zoe; Preston, Sally; Hanson, Andy; Gallagher, Peter; Harmer, Catherine J.; McAllister-Williams, R. Hamish
ABSTRACT: Little is known of the retest reliability of emotional cognitive tasks or the impact of using different tasks employing similar emotional stimuli within a battery. We investigated this in healthy subjects. We found improved overall performance in an emotional attentional blink task (EABT) with repeat testing at one hour and one week compared to baseline, but the impact of an emotional stimulus on performance was unchanged. Similarly, performance on a facial expression recognition task (FERT) was better one week after a baseline test, though the relative effect of specific emotions was unaltered. There was no effect of repeat testing on an emotional word categorising, recall and recognition task. We found no difference in performance in the FERT and EABT irrespective of task order. We concluded that it is possible to use emotional cognitive tasks in longitudinal studies and combine tasks using emotional facial stimuli in a single battery.